Recent interventions to improve retention in HIV care and adherence to antiretroviral treatment among adolescents and youth: a systematic review. - Casale, M; Carlqvist, A; Cluver, L (Mary Ann Liebert Inc. Publishers, 2019)
Adolescents represent a growing proportion of people living with HIV worldwide and the highest risk population group for treatment attrition and AIDS-related mortality. There is an urgent need to design, implement, and test interventions that keep young people in HIV treatment and care. However, previous systematic reviews show scarce and inconclusive evidence of effective interventions for this age group. Recent years have seen an increase in focus on adolescent health and a rapidly changing programmatic environment. This systematic review article provides an evidence update by synthesizing empirical evaluations of interventions designed to improve antiretroviral therapy adherence and retention among adolescents (10-19) and youth (15-24) living with HIV, published between January 2016 and June 2018. A search of 11 health and humanities databases generated 2425 citations and 10 relevant studies, the large majority conducted in sub-Saharan Africa. These include six clinic-level interventions, one individual-level m-Health trial, and three community- or household-level interventions. Implications of their findings for future programming and research with young adults are discussed, in relation to previous reviews and the broader empirical evidence in this area. Findings highlight the need to further develop and test multi-faceted interventions that go beyond health facilities, to address broader social barriers to adherence and retention. In particular, further intervention studies with adolescents (10-19) should be a priority, if we are to retain these young people in treatment and care and aspire to achieve the United Nation's Sustainable Development Goals and 90-90-90 targets.